2021
DOI: 10.1042/cs20210049
|View full text |Cite
|
Sign up to set email alerts
|

C21 preserves endothelial function in the thoracic aorta from DIO mice: role for AT2, Mas and B2 receptors

Abstract: Compound 21 (C21), a selective agonist of angiotensin II type 2 receptor (AT2R), induces vasodilation through NO release. Since AT2R seems to be overexpressed in obesity, we hypothesize that C21 prevents the development of obesity-related vascular alterations. The main goal of the present study was to assess the effect of C21 on thoracic aorta endothelial function in a model of diet-induced obesity (DIO) and to elucidate the potential cross-talk among AT2R, Mas receptor (MasR) and/or bradykinin type 2 receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 53 publications
3
8
0
Order By: Relevance
“…It is important to note that studies of our group have previously revealed vascular alterations, including endothelial dysfunction and a defective NO release, in mice fed a HF diet for 6 weeks. [17][18][19] The main findings of this study are that restoring a healthy diet for a period as short as 2 weeks after HF diet intake was enough to reduce BW and improve metabolic parameters, endothelial function, and AMPKderived vascular responses in the thoracic aorta, due to the activation of the AMPK/CREB signaling pathway.…”
Section: Discussionmentioning
confidence: 83%
“…It is important to note that studies of our group have previously revealed vascular alterations, including endothelial dysfunction and a defective NO release, in mice fed a HF diet for 6 weeks. [17][18][19] The main findings of this study are that restoring a healthy diet for a period as short as 2 weeks after HF diet intake was enough to reduce BW and improve metabolic parameters, endothelial function, and AMPKderived vascular responses in the thoracic aorta, due to the activation of the AMPK/CREB signaling pathway.…”
Section: Discussionmentioning
confidence: 83%
“…29,30 In our model, C21-mediated activation of iBAT in HFD-fed mice did not modify body mass, but successfully reduced circulating insulin levels. In addition, previous reports from our group in these animals showed that C21 preserves the endothelial function in thoracic and abdominal aorta from obese mice, 26,27 demonstrating a role in cardiovascular protection. According to our results, C21 enhances BAT activity in obese mice by (i) enhancing thermogenesis via ETC and UCP1 upregulation; (ii) increasing BAT mass through a promotion of cell differentiation, and (iii) improving BAT function through a reduction in inflammation and oxidative stress.…”
Section: Discussionmentioning
confidence: 59%
“…Potentiating the brown characteristics of PVAT has been proposed to exert protective effects in the aorta 12,42 . In fact, using a similar methodological approach, we have already described the beneficial effects of AT2R activation by C21 in the thoracic aorta of obese animals 43 . C21 prevented the development of obesity‐induced endothelial dysfunction by stimulating NO release through PKA/p‐eNOS and AKT/p‐eNOS pathways.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations